2018
DOI: 10.3389/fpsyg.2018.02067
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-Focused Dance Movement Therapy Assessment Enhanced by iPad App MARA

Abstract: Healthcare and human services are increasingly required to demonstrate effectiveness and efficiency of their programs, with assessment and evaluation processes more regularly part of activity cycles. New approaches to service delivery, such as the National Disability Insurance Scheme (NDIS) scheme in Australia, require outcome-focused reporting that is responsive to the perspectives of clients. Eco-systematic approaches to service delivery and assessment consider the client as part of an interconnected web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Most of the studies were published in the last decade (n = 24); the remaining studies were published between 1997 and 2010. In 29 studies, a single case design was used (Dunphy & Hens, 2018;Gaskin et al, 2012;Hetzroni & Banin, 2017;Hronis et al, 2019;Kim et al, 2014;;Lancioni, Singh, O'Reilly, Green, et al, 2014;Lancioni, Singh, O'Reilly, Sigafoos, et al, 2014;Perilli et al, 2019;Simacek et al, 2017;Singh et al, 2017;Stasolla et al, , 2015Stasolla et al, , 2017aStasolla, Perilli, Caffò, et al, 2017;. In addition, two studies used a pre-experimental design (Hoffman et al, 2017;Jonker et al, 2015) and one study used a randomized control trial (Cooney et al, 2017), while one study did not report about the study design (Monlux et al, 2019).…”
Section: Re Sultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies were published in the last decade (n = 24); the remaining studies were published between 1997 and 2010. In 29 studies, a single case design was used (Dunphy & Hens, 2018;Gaskin et al, 2012;Hetzroni & Banin, 2017;Hronis et al, 2019;Kim et al, 2014;;Lancioni, Singh, O'Reilly, Green, et al, 2014;Lancioni, Singh, O'Reilly, Sigafoos, et al, 2014;Perilli et al, 2019;Simacek et al, 2017;Singh et al, 2017;Stasolla et al, , 2015Stasolla et al, , 2017aStasolla, Perilli, Caffò, et al, 2017;. In addition, two studies used a pre-experimental design (Hoffman et al, 2017;Jonker et al, 2015) and one study used a randomized control trial (Cooney et al, 2017), while one study did not report about the study design (Monlux et al, 2019).…”
Section: Re Sultsmentioning
confidence: 99%
“…The vast majority of the studies (n = 29) reported on interventions that were delivered at the individual level (Cooney et al, 2017;Dunphy & Hens, 2018;Gaskin et al, 2012;Hoffman et al, 2017;…”
Section: Characteristics Of the Psychological Ehealth Interventionsmentioning
confidence: 99%
See 3 more Smart Citations